A Sequência Fedathi e o ensino de sólidos geométricos - Lopes, João Paulo Benevides (2015)
The teaching of mathematics, and in particular the geometry, presents today still a challenge to educators in the pursuit of promoting better learning rates and therefore school success in this discipline. In this sense, the present work deals with the application of Fedathi Sequence methodology in the teaching of geometric solids. It began with a bibliographical research aimed at understanding on the geometry and its teaching, as well as the methodological foundation of Fedathi Sequence. It also outlined as a field of research that analyzed the pedagogical potential of this method in teaching and learning of geometric solids. Had as research subjects two classes of the 2nd year of high school the EEM Iguatu-Ce High School José Gondim, which were divided: one control group and the other where the research was conducted. In the latter, the teaching of geometric solids has worked in the light of Fedathi sequence. It had a population of 45 students, of which 43 of them responded to the pre-test questionnaire (containing the requirements of the given content), while 42 answered the post-test questionnaire and socioeconomic questionnaire. In the control group had a population of 40 students, with a sample of 38 of them responded to the pre-test questionnaire and 35 to the post-test questionnaires and socioeconomic. The latter questionnaire was closed and aimed to characterize the subjects. Already the pre-test and post-test questionnaires, which also composed the research techniques were semi-structured and sought to assess the students' learning outcomes. Were also made records of the educational sessions planning, plan summary of each session and produced recordings of each teaching session. The field research revealed that in addition to geometric solids concepts apply to the methodology of Fedathi Sequence, teaching this content ruled this sequence favored the better learning outcomes when compared to the control group.